2021
DOI: 10.51620/0869-2084-2021-66-11-689-694
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic manifestations of tickborne mixed infection in combination with COVID-19

Abstract: The coexistence of various pathogens inside the patient’s body is one of the poorly studied and current issues. The aim of the study is to identify the relationship between the indicators of complex laboratory diagnostics and the clinical manifestations of a mixed disease during subsequent infection with the SARS-CoV-2 virus using the example of a case of chronic encephalitis-borreliosis infection. Seven blood serum samples were collected from the patient over the course of a year. For the etiological verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Anti-COVID-19 treatment included umifenovir, hydroxychloroquine, azithromycin, and ceftriaxone, and it resulted in suppression of borreliosis, as manifested by the first decrease of anti- Borrelia IgG in diagnostics. However, that report was not dedicated to possible effects of borreliosis on the course of COVID-19 17 . Piotrowski and Rymaszewska (2022) pointed out a reduced number of cases of Lyme disease registered during the COVID-19 pandemic in Poland, and they concluded that it may result from limited outdoor activities in the lockdown, but possibly also from poor access of patients to the overburdened health care system 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-COVID-19 treatment included umifenovir, hydroxychloroquine, azithromycin, and ceftriaxone, and it resulted in suppression of borreliosis, as manifested by the first decrease of anti- Borrelia IgG in diagnostics. However, that report was not dedicated to possible effects of borreliosis on the course of COVID-19 17 . Piotrowski and Rymaszewska (2022) pointed out a reduced number of cases of Lyme disease registered during the COVID-19 pandemic in Poland, and they concluded that it may result from limited outdoor activities in the lockdown, but possibly also from poor access of patients to the overburdened health care system 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Anti-COVID-19 treatment included umifenovir, hydroxychloroquine, azithromycin, and ceftriaxone, and it resulted in suppression of borreliosis, as manifested by the rst decrease of anti-Borrelia IgG in diagnostics. However, that report was not dedicated to possible effects of borreliosis on the course of COVID-19 17 . Piotrowski and Rymaszewska (2022) pointed out a reduced number of cases of Lyme disease registered during the COVID-19 pandemic in Poland, and they concluded that it may result from limited outdoor activities in the lockdown, but possibly also from poor access of patients to the overburdened health care system 18 .…”
Section: Introductionmentioning
confidence: 99%